2021
DOI: 10.1097/md.0000000000025718
|View full text |Cite
|
Sign up to set email alerts
|

PRISMA: accuracy of response entropy and bispectral index to predict the transition of consciousness during sevoflurane anesthesia

Abstract: Background: Bispectral index (BIS) and response entropy (RE) are used to monitor the depth of anesthesia. Objectives: To collect published data and compare the accuracy of BIS and RE in detecting the transition of consciousness during sevoflurane anesthesia. Data sources: Studies indexed in the PubMed, Embase, or Cochrane databases. Study eligibility criteria: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Otra herramienta para medir la profundidad anestésica es la entropía, se acepta que existe una ligera ventaja del BIS sobre este monitor para determinar la profundidad anestésica (66) .…”
Section: Bis Y Otros Monitores De Profundidad Anestésica Y Conscienciaunclassified
“…Otra herramienta para medir la profundidad anestésica es la entropía, se acepta que existe una ligera ventaja del BIS sobre este monitor para determinar la profundidad anestésica (66) .…”
Section: Bis Y Otros Monitores De Profundidad Anestésica Y Conscienciaunclassified
“…Sevoflurane inhalation anesthesia has been used for fiberoptic bronchoscopy in children because it induces rapid anesthesia without significantly affecting voluntary breathing. However, it has been reported that sevoflurane can easily lead to pediatric anesthesia emergence delirium (PAED), which is not conducive to children's postoperative recovery and may cause concern for parents (3). Esketamine, a novel intravenous anesthetic drug, is the dextro-isomer of ketamine.…”
Section: Introductionmentioning
confidence: 99%